Real-time hybrid simulation framework for the investigation of soil-structure interaction effects on the vibration control performance of shape memory alloys. (15th September 2021) - Ding, Hao; Kaup, Andreas; Wang, Jin-Ting; Lu, Li-Qiao; Altay, Okyay
Graphical abstract: Highlights: A cyber-physical real-time hybrid simulation based methodology is proposed. Soil-structure interaction effects are considered with a finite-element soil model. The vibration control performance of shape memory alloys is investigated. The mathematical description and the hardware configuration are introduced. The proposed methodology is applied to a controlled shear frame structure. Abstract: Shape memory alloys (SMAs) are two-phase polycrystal smart materials with hysteretic energy dissipation capacity. Under a mechanically applied strain, SMAs can transform their phases and recover large deformations in a superelastic fashion. Both the hysteretic damping and the deformation recovery are key features for new type of maintenance-free vibration control devices. Various factors influence the energy dissipation process of SMAs. Particularly rates and amplitudes of the applied deformation pattern are crucial for the damping. The studies have focused so far on the interaction between structures and SMAs. This paper goes one step further and seeks to consider the soil-structure interaction (SSI) in the treatment of the SMA control performance as well. A real-time hybrid simulation based cyber-physical methodology is developed for this purpose. Using finite-element modeling technique, a semi-infinite boundary definition is realized for the soil and the soil-foundation interaction is replicated for SMA-controlled structures. The proposed approach is applied to a shear frame structure equipped with SMA wires. The responses of the structure to historic earthquake records are assessed from a macroscopic perspective of the SMA behavior. The study shows that the material and radiation damping of the soil-foundation interaction have a significant influence on the vibration control performance of SMAs.